Cattle classified - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The cattle of the Tropics provides information for students, research workers and others concerned with livestock improvement, by describing 300 breeds of cattle in the Tropics. It sets out a simple classification of the main types, Zebu, Sanga,...